Bonner Künstler aktuell. (Bonn : Städtisches Kunstmuseum Bonn, 1982)
Beisegel, Mona ; Benz, Wolfgang ; Bonato, Victor ; Brenig, Gi ; Burges, Michael ; Claassen, Udo ; Ebener, Wolf ; Eichner, Hellmuth ; Engelken, Dierk ; Garrels, Arno ; Jablonsky, Hilla ; Kaschel, Udo ; Kremer, K. Peter ; Loviscach, Margarete ; Meister, Dankward ; Mookerjee, Lila ; Nolte, Faustinus ; Palm, Goedart ; Parivartan, Swami ; Rast, Fredi ; etc.
Bonner Künstler aktuell, Städtisches Kunstmuseum Bonn, 28. April - 6. Juni 1982
boek